Rare bird documentation form for Lesser Black-backed Gull at Saylorville Reservoir, 1986 - Dinsmore, Stephen J.et al (1986)
Rare bird documentation form for a Lesser Black-backed Gull at Saylorville Reservoir in Polk County, IA on November 29, 1986. Epson - sheet feed